Post-Traumatic Recovery Using the Korpan Salt Mask - Bondar , Kateryna; Kohut , Оleksandra; Palant , Volodymyr (Insight: the psychological dimensions of society, 2025)
The aim of this study was to evaluate the therapeutic potential of the Korpan salt therapy mask combined with structured psychotherapeutic support for individuals affected by the war in Ukraine and presenting with symptoms of acute stress disorder, post-traumatic stress disorder, and anxiety. Methods. The study was grounded in an integrative, trauma-informed theoretical model that incorporates psychophysiological, psychological, and clinical approaches. It employed a mixed-methods design with both quantitative and qualitative data collection. The sample comprised 57 participants (27 adults and 30 children, predominantly internally displaced persons) who, over two-weeks, used the Korpan mask daily in combination with psychotherapy encompassing four stages: psychophysiological stabilization, emotional balance regulation, cognitive process restoration, and the development of constructive coping strategies. Quantitative assessment was conducted using the PSQI, HADS-A/D, PTSD Diagnostic Scale, and KM-SABS; qualitative data were obtained through semi- structured interviews and parent questionnaires for children. Results showed statistically significant improvements across all key indicators: an increase in parasympathetic dominance on the KM-SABS (+2.37; p < 0.01; r = 0.56), reductions in PTSD symptom severity (−2.11; p < 0.01; r = 0.65), anxiety (−5.30; p < 0.001; r = 0.68), and PSQI sleep disturbance scores (−3.30; p < 0.01; r = 0.56). Thematic analysis revealed four core recovery themes: physiological stabilization and improved sleep, reduced hyperarousal, enhanced emotional regulation and social interaction, and decreased trauma-related play and avoidance behavior. The synergy of sensory modulation, parasympathetic nervous system activation, and psychotherapy facilitated more rapid reduction of psychophysiological tension, easier engagement in the therapeutic process, and increased emotional resilience. Discussion and Conclusions. The use of the Korpan mask in combination with psychotherapeutic support represents a promising, accessible, and non-invasive tool for supporting mental health in low-resource and humanitarian crisis settings. The findings support the need for further large-scale controlled studies to confirm its effectiveness, explore long-term outcomes, and integrate this approach into multimodal trauma-informed care programs.
Keywords: Array; Array; Array; Array; Array